2015
DOI: 10.1016/j.colsurfa.2014.12.058
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of distinct nanofibrillated celluloses assessed by inverse gas chromatography

Abstract: Surface properties of distinct nanofibrillated celluloses assessed by inverse gas chromatography, Colloids and Surfaces A: Physicochemical and Engineering Aspects (2015), http://dx.doi.org/10.1016/j.colsurfa. 2014.12.058 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
(46 reference statements)
6
15
0
Order By: Relevance
“…Consistent with the Lindman hypothesis, both samples are amphoteric (Lindman et al 2010) (Table S1), both powders feature higher dispersive surface energies than cotton (Kondor et al 2015) and lyocell fibers (Tze et al 2006) and are comparable to TEMPO-oxidized and genuine CNF (Peng et al 2013;Gamelas et al 2015).…”
supporting
confidence: 65%
“…Consistent with the Lindman hypothesis, both samples are amphoteric (Lindman et al 2010) (Table S1), both powders feature higher dispersive surface energies than cotton (Kondor et al 2015) and lyocell fibers (Tze et al 2006) and are comparable to TEMPO-oxidized and genuine CNF (Peng et al 2013;Gamelas et al 2015).…”
supporting
confidence: 65%
“…For the unmodified xylan a decreasing trend of the γ s d value with temperature in the range of studied temperatures (40-55°C) was found (Fig. 4), as previously observed for related cellulosic materials [35,42]. For the CMX the variation of the γ s d value with temperature (in the same temperature range) was somewhat different: it decreased from 40 to 45°C and then reached a plateau (Fig.…”
Section: Surface Properties Assessed By Inverse Gas Chromatographysupporting
confidence: 59%
“…In the 1500-1700 cm −1 region, bands at 1600 cm −1 and ca. 1645 cm −1 (shoulder) from ionized glucuronic acid groups and sorbed water, respectively, were also observed [33][34][35]. For CMX (Fig.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 83%
See 1 more Smart Citation
“…No previous studies of the surface of this type of materials by IGC were found in the literature. However, the γ s d values are comparable with those of chitosan or alginate alone or of other polysaccharides, such as cellulose and hemicelluloses . For instance, a 80% deacetylated chitosan presented a γ s d value of 46 mJ·m −2 at 50°C and sodium alginate showed a γ s d value of 39 mJ·m −2 at 25°C.…”
Section: Resultsmentioning
confidence: 78%